Relationship between benzodiazepine prescription, aggressive behavior, and behavioral disinhibition: a retrospective study in a Swiss prison - Stéphanie Baggio; Vladan Starcevic; Patrick Heller; Karen Brändle; Irina Franke; Andreas Schneeberger; Anna Buadze; Alex Gamma; Roman Schleifer; Laurent Gétaz; Hans Wolff; Michael Liebrenz (BMC, 2021)
Abstract Background Benzodiazepines are commonly prescribed in prisons amidst the controversies surrounding their potential role in causing behavioral disinhibition and aggressive behavior and their association with use and trafficking of illicit and addictive substances. The present study aimed to (1) ascertain the relationship between benzodiazepine prescription (including their dosage and duration of use) and aggressive behavior and behavioral disinhibition in prison and (2) investigate whether there was an association between benzodiazepine prescription, (including their dosage and duration of use) and using and trafficking illicit and addictive substances during imprisonment. Methods Data were extracted from the electronic database of an "open" Swiss prison (n = 1206, 1379 measures) over a 5-year period (2010-2015). Measures included benzodiazepine prescription, duration of benzodiazepine use and mean dosage, and punishable behaviors (physical and verbal aggression, disinhibited but not directly aggressive behaviors, property damage or theft, substance-related offenses, and rule transgression). We assessed the relationship between benzodiazepine prescription and punishable behaviors after propensity score matching. Logistic regressions were also used to test the relationship of benzodiazepine use duration and dosage with punishable behaviors among participants who received benzodiazepines. Results After propensity score matching, benzodiazepine prescription was not significantly associated with any punishable behavior. Among detained persons who took benzodiazepines, there was no significant association of dosage and duration of use with offenses involving illicit or addictive substance use or trafficking. Conclusions Our study did not empirically support the occurrence of increased aggressive or disinhibited behaviors or increased risk of substance abuse in detained persons who received benzodiazepines in prison. This suggests a need to reconsider restrictions in prescribing benzodiazepines in the prison setting.